Investigating the evolution of the technologies for collecting microplastics. (15th January 2023) - Spreafico, Christian; Russo, Davide
Abstract: To stop the dispersion of microplastics in the ecosystem, many technologies for collecting them were designed, tested and developed in the last period. However, a complete and exhaustive comparison of these technologies to guide in the choice and/or in the development of the most suitable appropriate one is missing in the literature. This study investigates the presence of some known technological trends, deriving from the TRIZ (Russian acronym for "Theory of Inventive Problem Solving") in the behaviour (i.e. the operating principle) of these technologies. To do this, a systematic methodology was followed, which has a general value and consists in analysing the patents relating to these technologies through various bibliometric indexes (i.e. Innovation index, Emergence Score index, Independent Claims index and Technology Cycle Time index). In general, the obtained results did not reveal a clearly identifiable ranking of the behaviour which was unanimously confirmed by all the considered bibliometric indexes. In addition, the average of the scores of the different indexes associated with the different behaviours equalized their differences. However, these results are mainly due to the markedly different evaluations obtained by the Emergence Score index compared to those of the other indexes. From the comparison of the results with the evolutionary trends, it emerged that the operative zone reduction trend was the most confirmed, while the technical system dematerialization was the least confirmed by the bibliometric analysis of all the indexes. In particular, the ranking of the behaviours provided by the Innovation index best confirmed all the evolutionary trends, while that of the Emergence Score index was the worst. In conclusion, this study confirmed the adherence of the development that technologies for collecting microplastics are following to the evolutionary trends through bibliometric analysis: this sequence places magnetic technologies in first place, followed by chemical, fluid dynamics, dynamic mechanics and static mechanics. The analysis of the performances declared in the patents substantially confirms this result. Graphical abstract: Image 1 Highlights: Ranking the technologies for collecting microplastics through bibliometric indexes. Comparing the rankings with known technological evolutionary trends. Emerged ranking for collection is: magnetic, chemical, fluid dynamic and mechanical. Confirming bibliometric trends with the analysis of the performances.